2012
DOI: 10.5194/bgd-9-10241-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Carbon fluxes forced by anticyclonic mesoscale eddies generated by islands at the subtropical NE Atlantic Ocean

Abstract: The carbon fluxes mediated by planktonic communities in two cyclonic eddies (CEs) and two anticyclonic eddies (AEs) at the Canary Eddy Corridor were studied and compared with the dynamics in two far-field (FF) stations located outside the eddies. We observed favorable conditions and signs for upwelling at the center of CEs and for downwelling and mixing at the centers of AEs. CEs were characterized by higher nutrients concentration and highest chlorophyll <i>a</i> concentration, associated with hig… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Higher concentrations of chlorophyll-a and nutrients, as well as OC production, were typically observed in a CE than those of an anticyclonic eddy (ACE) (Sarma et al, 2019b). Higher production of dissolved OC (DOC) was also reported in either an earlystage or decaying-stage ACE ecosystem (Lasternas et al, 2012;. The surface water of ACEs containing high DOC and particulate OC (POC) were transported into deeper layers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher concentrations of chlorophyll-a and nutrients, as well as OC production, were typically observed in a CE than those of an anticyclonic eddy (ACE) (Sarma et al, 2019b). Higher production of dissolved OC (DOC) was also reported in either an earlystage or decaying-stage ACE ecosystem (Lasternas et al, 2012;. The surface water of ACEs containing high DOC and particulate OC (POC) were transported into deeper layers.…”
Section: Introductionmentioning
confidence: 99%
“…The surface water of ACEs containing high DOC and particulate OC (POC) were transported into deeper layers. At the depth decomposition of POC and consumption of DOC greatly affect OC composition, contributing to the oceanic carbon pool and carbon pump (Kolasinski et al, 2012;Lasternas et al, 2012). Recently, observations in Bay of Bengal indicated that mesoscale eddies could change patterns of carbon sources and sinks by vertical and horizontal water mixings (Sarma et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Very few factors substantially suppressed carbon export, except for the mesoscale anticyclonic eddy (Lasternas et al, 2012). Our SSHA data ( Figure 4G) exceeded 0.07 m at the beginning of July, directly suggesting the influence of the anticyclonic eddy (Roemmich and Gilson, 2001;Huang et al, 2010).…”
Section: Small Values In Summer Induced By Anticyclonic Eddymentioning
confidence: 69%
“…Based on the Bermuda Atlantic Time-series Study of the Sargasso Sea, Sweeney et al (2003) clearly showed that the 1994 spring bloom was suppressed by the passage of anticyclonic eddies with SSHA around 0.20 m. In the Norwegian Sea, warmcore eddies could delay the phytoplankton bloom by about 2 weeks (Hansen et al, 2010). Lasternas et al (2012) not only observed a considerable enhancement of dissolved organic carbon (DOC) concentration in the anticyclonic eddy center, but also diatom cell mortality rates of 60%. They proposed that the high mortality and cell lysis rates mainly resulted in the DOC increase, thereby reducing carbon export.…”
Section: Small Values In Summer Induced By Anticyclonic Eddymentioning
confidence: 99%
“…In the northern hemisphere, most anticyclonic systems are oligotrophic, with nutrient-poor surface waters and restricted primary production. However, anticyclonic eddies (ACEs) are usually associated with relatively abundant microorganisms, an appreciable growth rate and DOC (dissolved organic carbon) accumulation (Bidigare et al, 2003;Ewart et al, 2008;Baltar et al, 2010), possibly triggered by downwelling in early-stage anticyclonic systems (Lasternas et al, 2012). DOC-rich surface waters and particulate organic carbon (POC) in ACEs were downwelled into deeper layers where extensive biogeochemical processing greatly affected its composition and the contributions of DOC to the oceanic carbon pump (Kolasinski et al, 2012;Lasternas et al, 2012).…”
Section: Introductionmentioning
confidence: 99%